PENGARUH PENGGUNAAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLES BERBASIS KONTEKSTUAL TERHADAP PEMAHAMAN MATEMATIKA PESERTA DIDIK - KHOLIS, SITI NUR; Edy, Sarwo; Suryanti, Sri (Universitas Muhammadiyah Gresik, 2023)
The purpose of this study was to determine the effect of using a learning model using the contextualbased Example non Examples method on students understanding of matemathics. The type of research used is Quantitative Research with a correlational research desighn, namely a study to determine the influence and level of influence between two or more variables. The sample in this study were 32 students, with data cllection techniques using observation instruments and questionnaires. The results of this study indicate that there is an affect of using the example non examples learning model on students understanding of matemathic, this is evindenced by the average value of control class is 65 and experience class is 85. The conclusion of this study can show that the ability to understand matemathics of students who are taught by applying the example non examples learning model is better than just using the conventional / lecture method. Keyword: learning models, example non Examples, student understanding